2018
DOI: 10.1080/2162402x.2017.1423170
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression is regulated by both DNA methylation and NF-kB during EMT signaling in non-small cell lung carcinoma

Abstract: Tumor cells, which undergo Epithelial-mesenchymal transition (EMT) acquire increased capacities of proliferation, invasion and have the ability to generate metastases by escaping the immune system during their systemic migration. To escape the immune system, cancer cells may induce tolerance or resist elimination by immune effectors multiple mechanisms and we hypothesized that EMT may control the expression of immune checkpoint inhibitors, then promoting immune evasion. PD-L1 (programmed cell death ligand 1) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
158
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 54 publications
8
158
1
Order By: Relevance
“…Thus, PD-L1 promoter methylation may provide a potentially more effective immunotherapeutic strategy in some tumor patients. Since PD-L1 overexpression transiently occurs during the cytokine-driven epithelial mesenchymal transition (EMT), a strong link between PD-L1 promoter demethylation and the TGF-β signaling pathway was found, which was associated with the loss of DNA methyltransferase 1 (DNMT1) in lung cancer cells [96].…”
Section: Epigenetic Deregulation Of Pd-l1 In Tumorsmentioning
confidence: 99%
“…Thus, PD-L1 promoter methylation may provide a potentially more effective immunotherapeutic strategy in some tumor patients. Since PD-L1 overexpression transiently occurs during the cytokine-driven epithelial mesenchymal transition (EMT), a strong link between PD-L1 promoter demethylation and the TGF-β signaling pathway was found, which was associated with the loss of DNA methyltransferase 1 (DNMT1) in lung cancer cells [96].…”
Section: Epigenetic Deregulation Of Pd-l1 In Tumorsmentioning
confidence: 99%
“…Notably, certain studies have elucidated that in human melanoma, PD-L1 expression may be altered by DNA hypomethylating agents (29). Moreover, the expression level of PD-L1 can be regulated using DNA methylation, in response to NF-κB or transforming growth factor-β signaling in NSCLC (30). In the current study, the PD-L1 methylation status correlated with PD-L1 protein expression and the number of lymph node metastases, implying that methylation of the PD-L1 promoter may affect tumor progression in advanced gastric cancer tissues, via the regulation of protein expression.…”
Section: Pd-l1 Promoter Methylationmentioning
confidence: 99%
“…These data indicate that increased expression of PDL1 with age most directly associates 18 with age-related increases in tumor mutational burden. 19 20 Due to previous work suggesting that DNA methylation regulates tumor expression of PDL1 21 (Asgarova et al, 2018), (Micevic et al, 2019), we hypothesize that the observed expression 22 increases of immune checkpoint genes are largely driven by epigenetic changes. We leverage 23 merged 450k and 27k methylation array data from TCGA (Thorsson et al, 2018) and find that 24 methylation of CpGs annotated to the PDL1 promoter region significantly decreases with age 25 pan-cancer (q = 3.27 x 10 -10 ), including cancer type as a covariate.…”
mentioning
confidence: 99%